A Pseudopotential Lattice Boltzmann Analysis for Multicomponent Flow (Communications in Computational Physics, 2022)
This paper presents a pseudopotential lattice Boltzmann analysis to showthe deficiency of previous pseudopotential models, i.e., inconsistency between equilibrium velocity and mixture velocity. To rectify this problem, there are two strategies: decoupling relaxation time and kinematic viscosity or introducing a system mixture relaxation time. Then, we constructed two modified models: a two-relaxation-time (TRT) scheme and a triple-relaxation-time (TriRT) scheme to decouple the relaxation time and kinematic viscosity. Meanwhile, inspired by the idea of a systemmixture relaxation time, we developed three mixture models under different collisionschemes, viz. mix-SRT, mix-TRT, and mix-TriRT models. Afterwards, we derived theadvection-diffusion equation for the multicomponent system and derived the mutualdiffusivity in a binary mixture. Finally, we conducted several numerical simulations tovalidate the analysis on these models. The numerical results show that these modelscan obtain smaller spurious currents than previous models and have a wider range forthe accessible viscosity ratio with fourth-order isotropy. Compared to previous models, present models avoid complex matrix operations and only fourth-order isotropy isrequired. The increased simplicity and higher computational efficiency of these models make them easy to apply to engineering and industrial applications.